Study Of CuZnFerrite and Ferrofluid In The Flow Injection Synthesis - SasitoSarwodidoyo, Edie (Advances in Social Sciences Research Journal, 2017)
Ferrofluid is a nanoscale materials that are easy to make but of easily made these materials have physical properties that are relatively easy to change. Originally made of magnetite ferrofluid and are now able to be made in such a wide variety, and various kinds of physical properties caused. Ferrofluid will be made with basic ingredients CuZnFerrite.One process to do step wise such as Flow Injection Synthesis-FIS, to result material previously. This material is relatively toxic, but weakly. Of the various variants turns out there are two ingredients that have almost the same compound but the physical properties are extremely different. Such materials Bath088P and Bath09P.Bath088P of magnetic properties of ferromagnetic character and character Anti-ferromagnetic Bath09P.This situation is favorable for the division of tasks and responsibilities Bath088 can be directed into a ferrofluid, both cannot stable mixing, if mixing used strong magnetic to separately.